TRADISI UANG PANAIK DALAM PERKAWINAN SUKU BUGIS PADA MASYARAKAT DESA SANGLAR KECEMATAN RETEH KABUPATEN INDRAGIRI HILIR - Agustar "; Syamsul Bahri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The research is an analysis in social phenomena which occours in the implematation Uang Panaik on society Sanglar village. Uang Panaik is the main requirement in stepping into the marriage procession. Therefore the research aims to determine position bride price in the marriage of the Bugis tribe. And to know the implementation bride price the happened in society bugis tribe said. The research do sanglar Sanglar village Kecematan Reteh Kabupaten Indragiri Hilir which is a resident the larges ethnic Bugis in Provinsi Riau. Theory used Radcliff-Brown that is function concept and social structure. Data analysis done by way of approarch qualitative descriptive, data retrieval techniques in the research using purposive sampling the number of these 7 people is traditional adat, humanist, society directly involved bride price in the implementation. From the field research result that bride price has shifted to its true meaning who used to be is a form of appreciation against women function party money,but this has shifted be social prestige and longer Uang Panaik the higher it is. In the case impact on a individual or group as social prestige, social psychology, wedding canceled and silariang. It is characterized by such occurrences in the soceityKey word : Culture, Uang Panaik, Social Pricetage